AWARENESS OF HUSBANDS REGARDING BIRTH PREPAREDNESS AND COMPLICATION READINESS IN DISTRICT RAWALPINDI - Gilani, Dr. Rehma; Azam, Dr. Naila; Kamran, Dr. Javeria; Ihsan, Dr. Sidra; Atif, Dr. Rabia (Pakistan Armed Forces Medical Journal, 2019)
Objective: To determine knowledge, attitude and practices of husbands regarding birth preparedness and complication readiness.Study Design: Descriptive Cross-sectional study.Place and Duration of Study: Tehsil Kallar Sayden, Rawalpindi district, from Jul 2016 to Dec 2016.Material and Methods: Data was collected using a pre-structured questionnaire from 450 husbands of 20 to 55 years age group through multi stage sampling.Results: Statistical analysis showed 370 (83%) husbands had adequate knowledge, 425 (95%) had positive attitude while only 246 (55%) husbands had good practices. Socio-demographic characteristics of husbands showed statistical association with their knowledge and practices.Conclusion: The study identified barriers responsible for the gaps between knowledge and practices of husbands regarding birth preparedness and complication readiness and proposes recommendation for engagement of men in maternal health.